Ten Problems for Latin American Testimonialistas: Genres of a Continent's Proper Literature in the '60-'70s (Castilla. Estudios de Literatura, 2013)
The paper studies the generic reconfigurations of Latin American literary field during the 60-70’s, which led to the introduction of ‘testimonio’ as the regional literature’s “proper” genre, questioning the privileged status so far holded by the novel. With Angel Rama’s “Diez problemas para el novelista latinoamericano”, appeared in Casa de las Américas in 1964, as a starting point, we examine some problematic implicatons of novel writing in Latin-America, in good part linked to the regional field actors’ will to provide literature with a political meaning. Correlatively, we analize the continuities and ruptures between Rama’s essay and the critical discourse on the testimonial genre, equally promoted by Casa de las Américas, in order to show how such problematic implications reappear concerning testimonio, with both new alternative solutions and new open questions that, even within its recent critical approaches, define the historical signification of the genre.